2019
DOI: 10.3389/fcimb.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the Gut Microbiota and Their Correlation With Inflammatory Factors in Chronic Kidney Disease

Abstract: Alterations to the gut microbiota have been previously suggested to be tightly linked to chronic systemic inflammation, which is a major contributing factor to complications and disease progression in chronic kidney disease (CKD). Nevertheless, the effect of gut dysbiosis on the pathogenesis and/or production of inflammatory factors in CKD has not been extensively studied to date. In the present study, we conducted 16S ribosomal DNA pyrosequencing using fecal microbiota samples and analyzed the production of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
185
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 33 publications
15
185
2
2
Order By: Relevance
“…Bacteroides is one of the most abundant bacterial genera in the gut of healthy adults and patients with CKD [60]. Enrichment of aerobic bacteria in the colon of patients with CKD has been frequently reported [23,29,30,61,62], and was also confirmed in the present study (i.e., Enterobacteriaceae and E. coli).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Bacteroides is one of the most abundant bacterial genera in the gut of healthy adults and patients with CKD [60]. Enrichment of aerobic bacteria in the colon of patients with CKD has been frequently reported [23,29,30,61,62], and was also confirmed in the present study (i.e., Enterobacteriaceae and E. coli).…”
Section: Discussionsupporting
confidence: 87%
“…In a previous sequence-based comparison of the gut microbiota between patients with CKD stages 1 to 5 and non-CKD controls; however, higher Lactobacillus spp. levels in CKD were found [60]. Another health-promoting bacterial species is Akkermansia muciniphila, an essential propionate-generating and mucus-degrading species that is beneficial through the production of energy from mucus degradation and as such supporting the growth of butyrate-producing bacteria [60,[67][68][69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Chinese study observed no significant differences in intestinal flora diversity between CKD patients and healthy control groups, suggesting that bacterial diversity was not seriously damaged in this population [14]. Microbiota dysbiosis, which was differed between modes of dialysis, was considered a main risk factor in promoting chronic systemic inflammation in CKD patients [22]. Besides dialysis modes, age and dialysis vintage also contributed to the microbiome diversity [20].…”
Section: Discussionmentioning
confidence: 91%
“…In theory, the in ux of uremic toxins and urea into the gastrointestinal lumen provoke the overgrowth of bacteria that produce urease, uricase, indole, and p-cresol forming enzymes, generating a vicious cycle of in ammation and oxidative stress in ESRD patients [22]. Increased abundance of phylum Verrucomicrobia [63] and family Enterobacteriaceae [13,64] in CKD patients has also been found. However, Actinobacteria phylum and Akkermansia genera are reduced in CKD patients [63] compared to ESRD patients.…”
Section: Discussionmentioning
confidence: 99%